UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING PADA MATA PELAJARAN PPKn KELAS X DI SMA NEGERI 2 SUNGAI RAYA - Nurul Fadilah; Bambang Budi Utomo; Thomy Sastra Atmaja (Universitas Tanjungpura, 2020)
AbstractThe problems found in this study are the lack of varied teachers in teaching, students who are less active and student learning outcomes are low. Conducting this research to overcome these problems by using snowball throwing learning models in PPKn subjects in class X IPS 1 of SMA Negeri 2 Sungai Raya with a descriptive method of class action research approach. This research was conducted at SMA Negeri 2 Sungai Raya in class X IPS 1 with a total of students of 31. Data collection techniques used were slim observation techniques, measurement techniques, and documentary study techniques with data collection instruments namely observation sheets, learning achievement tests and documentation. Data collected uses average and percentage calculations. This research was conducted with II cycle. In the first cycle, most of the students 'scores were 73.22, in the second cycle, students' learning values changed, namely 83.87. From this data analysis it can be shown that there is a development in the value of student learning by applying the learning model that has been mentioned. Keywords: Efforts, Learning Outcomes PPKn, Snowball Throwing